2018
DOI: 10.1038/s41598-018-21455-1
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Disrupts Autophagic Flux by Inducing Lysosomal Dysfunction in Gastric Cancer Cells and Increases Their Sensitivity to Cytotoxic Drugs

Abstract: NSAIDs inhibit tumorigenesis in gastrointestinal tissues and have been proposed as coadjuvant agents to chemotherapy. The ability of cancer epithelial cells to adapt to the tumour environment and to resist cytotoxic agents seems to depend on rescue mechanisms such as autophagy. In the present study we aimed to determine whether an NSAID with sensitizing properties such as indomethacin modulates autophagy in gastric cancer epithelial cells. We observed that indomethacin causes lysosomal dysfunction in AGS cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
1
31
1
Order By: Relevance
“…In addition, we found that treatment with ISL induced autophagy-associated signaling proteins mTOR and ULK1 were downregulated by ISL treatment, while the expressions of p62, Beclin1, and LC3 autophagy-promoting proteins were all increased. However, during autophagy progression, p62 was enclosed by autolysosome and degraded by cathepsin B in lysosomes [44], although both p62 and LC3 II levels were increased by ISL. Therefore, ISL influences p62 accumulation by reduced cathepsin B to inhibit autophagy by blocked phagolysosome formation.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we found that treatment with ISL induced autophagy-associated signaling proteins mTOR and ULK1 were downregulated by ISL treatment, while the expressions of p62, Beclin1, and LC3 autophagy-promoting proteins were all increased. However, during autophagy progression, p62 was enclosed by autolysosome and degraded by cathepsin B in lysosomes [44], although both p62 and LC3 II levels were increased by ISL. Therefore, ISL influences p62 accumulation by reduced cathepsin B to inhibit autophagy by blocked phagolysosome formation.…”
Section: Discussionmentioning
confidence: 93%
“…During this process p62 binds ubiquitinated proteins through its ubiquitin‐associated (UBA) domain and anchors to LC3 in the autophagosome membrane through its LC3‐interacting region (LIR) domain . Recent evidence suggests that the completion of autophagy relies on smooth autophagic flux and renewal of autophagosomes whereas dysfunction in the autophagy pathway leads to the accumulation of p62 and damaged proteins that possibly results in cell death …”
Section: Introductionmentioning
confidence: 99%
“…In addition to target cancer cells directly, applying specific agents that induce host immune defences to suppress tumour growth may improve therapeutic outcomes. Recently, lysosome-associated agents, such as chloroquine (CQ), have been implicated as chemo-sensitizers [ 10 , 11 ]. In fact, several clinical trials have evaluated the ability of CQ to enhance the efficacy of chemotherapy in a variety of cancer treatments (NCT00969306, NCT02432417) [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%